The Meaning Context in Fast Food Advertisement: Pragmatics Study - Rahmah, Leny Saili; Nurazizah, Wafie Siti; Ramadhina, Nurul Fadhilah; Zulfiah, Yufi; Fatimah, Vina Aulia (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research aims to interpret English advertisements containing a pragmatics context. This study uses a qualitative method, and the object of this study is several English fast food restaurant advertisements. The data in this study were collected by searching fast food restaurant advertisements, then grouping them pragmatically, and classifying them based on their pragmatic context. Researchers got eight pieces of data to be examined, and they are: the first is 'call your own time-out', which means 'Take time to enjoy the food offered in the advertisement'. The second is 'it'll blow your mind away', means 'You will be surprised by the size of the food in the advertisement'. The third is 'get fully charged', means 'The food offered in the advertisement will satisfy the reader. The fourth is 'think outside the bucket', which means ordered food outside the menu package. The fifth is 'Happy hour' means 'there is a 20% discount, in a certain period or time of the advertisement'. The sixth is 'Sure is good to have around', which means a delicious meal to enjoy with close friends. The seventh is 'talking can wait', means Do not let the distractions while enjoying the food. The last advertisement is `Look its waving at you' means 'The food is tempting to buy.